Analyzing a long dream series: what can we learn about how dreaming works? - Schredl, Michael (Taylor & Francis Group, 2024)
Analyzing a Long Dream Series provides an extraordinary insight into the richness and variability of dreams, considering over 12,000 dreams that have been recorded for more than 30 years.